MULTIPLE SCLEROSIS EXPLAINED: FROM PATHOPHYSIOLOGY TO DIAGNOSIS AND MANAGEMENT - Anna Rakoczy; Patrycja Walkiewicz; Karolina Ochyra; Martyna Bukała; Kornelia Pudło; Jowita Frydrych; Gabriela Godek; Karolina Ryba; Katarzyna Znamirowska; Klaudia Zacher (International Journal of Innovative Technologies in Social Science, 2025)
Multiple sclerosis (MS) is a chronic, autoimmune disease of the central nervous system that leads to the destruction of the myelin sheaths in the brain and spinal cord, resulting in progressive disability. It most commonly affects young adults, with a higher prevalence in women. The exact causes of MS remain unclear. It is believed that genetic and environmental factors, such as viral infections and vitamin D deficiency, play a significant role in the disease's development. MS typically follows a relapsing-remitting course, with periods of exacerbation and clinical improvement. The symptoms of MS are highly variable and depend on the location of demyelinating lesions. The onset of the disease may be asymptomatic. Early symptoms often include vision disturbances, paresthesia, and aphasia. In advanced stages, patients may experience spasticity, tremors, bowel and bladder dysfunction, sexual dysfunction, dizziness, cognitive impairments, and pain. Treatment of MS requires an individualized approach that combines pharmacotherapy with rehabilitation. Despite advances in therapy, the disease can still shorten life expectancy by several years and significantly impact the quality of daily functioning.Aim of the Study: The aim of this article is to present the current state of knowledge on multiple sclerosis, including a discussion of its causes, symptoms, diagnostic methods, and available therapeutic options.Materials and Methods: A review of the available literature of Google Scholar, PubMed.Results: Multiple sclerosis (MS) is a chronic, autoimmune inflammatory disease that leads to damage to the myelin sheaths in the central nervous system, resulting in a variety of neurological symptoms. The pathogenesis of the disease involves genetic, environmental, and immunological factors. Patients with MS experience a decline in quality of life, particularly in terms of social and professional functioning, due to progressive disability and psychological symptoms. Disease-modifying treatments (DMTs), and biologic drugs, significantly reduce the frequency of relapses and delay disease progression.